2022
DOI: 10.3389/fneur.2021.726561
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value and Risk Factors of Treatment-Related Lymphopenia in Malignant Glioma Patients Treated With Chemoradiotherapy: A Systematic Review and Meta-Analysis

Abstract: Background: Immunotherapy has shown promising therapeutic efficacy in various cancers but not gliomas. Circulating lymphocytes play critical roles in cancer control and responses to immune checkpoint inhibitors. Treatment-related lymphopenia has been associated with poor survival in patients with various tumors. This meta-analysis evaluated the risk and impact of lymphopenia in patients with glioma.Methods: The PubMed, Embase, Web of Science, and Cochrane Library databases were comprehensively searched. Eligib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 42 publications
1
12
1
Order By: Relevance
“…Lymphopenia has been observed to correlate with poor patient outcomes (9,36). In our study, contrary to previous studies, we initially observed a significant univariate correlation between post-radiation lymphopenia and improved survival (Supplementary Figure 1, Supplementary Table 2).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Lymphopenia has been observed to correlate with poor patient outcomes (9,36). In our study, contrary to previous studies, we initially observed a significant univariate correlation between post-radiation lymphopenia and improved survival (Supplementary Figure 1, Supplementary Table 2).…”
Section: Discussioncontrasting
confidence: 99%
“…Neutrophils have been associated with increased resistance to radiation and poor cancer patient outcomes. Furthermore, elevated neutrophil-to-lymphocyte ratios (NLR > 4.0) have also been observed to be a poor prognostic indicator in glioma patients (8)(9)(10). Thus, we evaluated the effects of neutrophils and neutrophilia on survival.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another explanation may be that not all the regimens used to treat our population are associated with a real lymphocytes dysfunction. In fact, the sample consisted of NEN patients treated with temozolomide and others previously receiving peptide receptor radioligand therapy (PRRT), which often result in deep, long-lasting low lymphocyte levels (30)(31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“… 14 ) It is well-known that temozolomide causes lymphopenia as part of myelotoxicity, and previous research indicates that the incidence of severe lymphopenia was 31.6% and that treatment-related lymphopenia is strongly correlated with poor overall survival, low response rate, and recurrences. 15 ) Furthermore, lymphopenia was reported to be a biomarker of impaired host immunity and a decreased low absolute lymphocyte count was a poor prognostic factor for patients with lymphoma and other cancers. 16 , 17 ) Thus, we postulate that lymphopenia might cause mild immunosuppressive status in our case, which might result in the development of non-Hodgkin's lymphoma.…”
Section: Discussionmentioning
confidence: 99%